Endoscopic Interventions for the Early and Remission Phases of Acute Biliary Pancreatitis: What are the More Concrete and Practical Situations for Performing Them? - Sho Hasegawa; Shinsuke Koshita; Yoshihide Kanno; Takahisa Ogawa; Toshitaka Sakai; Hiroaki Kusunose; Kensuke Kubota; Atsushi Nakajima; Yutaka Noda; Kei Ito (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The use of endoscopic intervention (EI) for acute biliary pancreatitis (ABP) remains controversial because the severity of biliary obstruction/cholangitis/pancreatitis is not reflected in the indications for early EI (EEI). Methods A total of 148 patients with ABP were included to investigate 1) the differences in the rate of worsening cholangitis/pancreatitis between the EEI group and the early conservative management (ECM) group, especially for each severity of cholangitis/pancreatitis, and 2) the diagnostic ability of imaging studies, including endoscopic ultrasound (EUS), to detect common bile duct stones (CBDSs) in the ECM group. Results No differences were observed in the rate of worsening cholangitis between the EEI and ECM groups, regardless of the severity of cholangitis and/or the existence of impacted CBDSs. Among patients without impacted CBDSs and moderate/severe cholangitis, worsening pancreatitis was significantly more frequent in the EEI group (18% vs. 4%, p=0.048). In patients in the ECM group, the sensitivity and specificity for detecting CBDSs were 73% and 98%, respectively, for EUS, whereas the values were 13% and 92%, respectively, for magnetic resonance cholangiopancreatography. Conclusions EEI should be avoided in the absence of moderate/severe cholangitis and/or impacted CBDSs because of the high rate of worsening pancreatitis. EUS can contribute to the accurate detection of residual CBDSs, for the determination of the need for elective EI.